The Potential of Ethanol Extract Tamarillo (Solanum betaceum) on B-Cell Lymphoma 2 Expression in Mice (Mus musculus) Lungs Exposed to Lead Acetate - Cantika Marcellin Princess Iswandi; Herley Windo Setiawan; Nurmawati Fatimah; Reny I’tishom; Mila Qurotul A'yuni (Jurnal Respirasi, 2026)
Introduction: Lead acetate, a toxic heavy metal compound, induces cellular and tissue injury primarily through oxidative stress. Exposure via inhalation or ingestion enables systemic absorption and distribution to target organs, particularly the lungs. One of the key anti-apoptotic proteins involved in maintaining cell survival is B-cell lymphoma 2 (Bcl-2). The administration of exogenous antioxidants represents a preventive approach to counteract the cytotoxic effects of lead, including the use of ethanol extract of tamarillo fruit. This study investigated the potential influence of tamarillo (Solanum betaceum) ethanol extract, known for its antioxidant content. Specifically, it examined its effect on Bcl-2 expression in the lung tissue of male mice exposed to lead acetate. Methods: This study used a true experimental design in a controlled laboratory setting. The specimens were divided into five groups: K0 served as the negative control, while K1 acted as the positive control and was treated with lead acetate at a dose of 0.075 g/kgBW. Group P1, P2, and P3 received lead acetate combined with ethanol extract of tamarillo at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW, respectively. Results: The findings showed that tamarillo ethanol extract significantly increased lung Bcl-2 expression in lead-exposed mice (p<0.05). B-cell lymphoma 2 expression increased progressively with higher extract doses compared with the positive control group. Conclusion: Administration of the tamarillo ethanol extract at 100 mg/kgBW was the most effective and provided protective effects on lung tissue.